An Analysis of Student Difficulties in Writing Descriptive at Eight Grade in SMP N 4 Muara Bungo - Lestari, renda (Journal Of Language Education and Development (JLed), 2020)
This Research is descriptive quantitative method. The subjects of the research are twenty five students of second grade at SMPN 4 Muara Bungo who are detected as having constraint in writing of descriptive text. This research is aimed to find out Second grade difficulties in writing of descriptive text and the cause. They are second grade especially VII.2. The test and questionnaire were used as the instruments of this research. The test was used to obtain the data about the Second grade difficulties in writing of descriptive text. Furthermore, the questionnaire ware used to obtain the data about the causes of the second grade difficulties in writing of descriptive text. The finding showed that the students find constraint in all point of scoring, the highest percentage is 87% of students have constraint in grammar, the second percentage are 80% of students have constraint in vocabulary and 70% of students have constraint in content, the third percentage is 69% of students have constraint in organizing, and the last percentage is 68% of students have constraint in mechanism. Whereas, the factors causing the Second Grade difficulties in writing mastery of descriptive text are learners’ background (81%), teaching technique (71%), and the learners’ environment (78%). Based on the data finding in this research, some suggestions are given to English teacher that the teacher should emphasize to solve the students’ constraint and also he should learn better to apply the techniques of teaching writing skill. Some suggestions are given to students learn more enterprising about English, especially about writing from descriptive text, pay attention to the teacher well when learning, and if anyone does not understand then ask the teacher.